2022
DOI: 10.3389/fpls.2022.963874
|View full text |Cite
|
Sign up to set email alerts
|

GWAS and RNA-seq analysis uncover candidate genes associated with alkaline stress tolerance in maize (Zea mays L.) seedlings

Abstract: Soil salt-alkalization is a common yet critical environmental stress factor for plant growth and development. Discovering and exploiting genes associated with alkaline tolerance in maize (Zea mays L.) is helpful for improving alkaline resistance. Here, an association panel consisting of 200 maize lines was used to identify the genetic loci responsible for alkaline tolerance-related traits in maize seedlings. A total of nine single-nucleotide polymorphisms (SNPs) and their associated candidate genes were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The NAC transcription factor is involved in abiotic stress responses in plants, including those to salinity, drought and low temperatures. Based on previous transcriptome data [36], we found that the ZmNAC89 gene was significantly induced by alkaline-salt Na 2 CO 3 stress. In this study, we identified ZmNAC89 as a transcription factor with transcriptional activation activity and localization in the nucleus.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The NAC transcription factor is involved in abiotic stress responses in plants, including those to salinity, drought and low temperatures. Based on previous transcriptome data [36], we found that the ZmNAC89 gene was significantly induced by alkaline-salt Na 2 CO 3 stress. In this study, we identified ZmNAC89 as a transcription factor with transcriptional activation activity and localization in the nucleus.…”
Section: Discussionmentioning
confidence: 77%
“…Previously, we analyzed differentially expressed genes in the maize transcriptome under alkaline-salt Na 2 CO 3 stress using second-generation high-throughput sequencing RNA-Seq technology [36]. We found that the ZmNAC89 gene significantly increased expression levels under stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…At the seedling stage, three and four significant QTLs were detected for the survival rate 10 days and 15 days after a salt treatment (100 mM NaCl), respectively, and the candidate gene VrFRO8 could lower the SOD content by influencing the Fe 2+ /Fe 3+ ratio under salt stress [ 20 ]. However, several hub genes related to the alkali response in other crops, such as LOC_Os03g26210 [ 21 ], LOC_Os11g37300 , LOC_Os11g37320 , LOC_Os11g37390 [ 22 ], LOC_Os09g25060 [ 4 ], Zm00001d038250 , and Zm00001d001960 [ 23 ], have not been reported in mung bean using the GWAS. Therefore, this limits us in the characterization of the genetic basis and molecular mechanism of alkali tolerance in mung beans.…”
Section: Introductionmentioning
confidence: 99%